The Silent Killer: Investigating the Influence of Stress on Cardiovascular Health of Diabetic Patients - Muhammad Talha Mumtaz, Mohammad Mustafa Farooq Khan, Muhammad Uzair, Maliha Aslam Khan, Ali Salman, Hamza Farooq Tajammal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: This study investigates impact of stress on cardiovascular health of diabetic patients. Methodology: In this cross sectional survey, 450 participants were recruited using non probability consecutive sampling. Data was collected using structured questionnaire from diabetic patients visiting different hospitals and clinics in the city for checkup. Results: Among the 450 diabetic patients, 110(24.4%) have Low perceived stress level, 200(44.4 %) have Mild, 100(22.2 %) have Moderate and 40(8.9 %) had High perceived stress level. With the increase in Stress level the level of LDL Cholesterol, HDL Cholesterol and Triglycerides were also increasing significantly. Significant association was also observed between healthy diet adherence and stress level among diabetic patients. Conclusion; According to the study, stress management plays a significant role in diabetes treatment and management. By prioritizing stress management for diabetic patients, healthcare providers can promote better health outcomes and reduce cardiovascular disease risk. Keywords: Psychological Stress, Cardiovascular, Diabetic Patients